"Eu, uma peça": o trabalho como pena alternativa - Onair Zorzal Correia Júnior (2016)
The Community Service Order (CSO) hás been viewed as the most significant criminal mode, regarding the modalities os penalties restricting rights. It is noticed that, from the promotion of actions to Penal Alternatives Policy, much has been discussed about the integrative ability of this modality, being taken in response to a human practice of social rehabilitations. Because of that, there is an orientation analysis linked to the characteristics of their role in criminological action without providing an understanding of the activies carried out by CSO doers. Hence, the goal of this research was to understand the meanings of the CSO penalty by the doers, as well as its resonance in their daily lives. Starting from the idea of the use of work as a punishment, it is considered that the criminal alternatives correspond currently to what Deleuze argues as practices of a society of control that uses freedom restraint as a spread to the social control. Being a qualitative research type, the study happened in a third sector institution of Vale do Aço region in the city of Santana do Paraíso, intending to approach the subjects through two methodological tools: observation and interviews. By using the theoretical background derived from two of the Work Clinics areas, Work Psychosociology and Ergonologics, and Critical Criminology, the research tried to get closer to the actual work performed by the subjects, in order to understand the meaning of the CSO in their identities and their daily lives. It was identified a tendency of criminalization in outskirts and in its neighborhood, as well as precarity amd work marginalization in outskirts and in its neighborhood, as well as precarity and work marginalization in the context of the subjects studied, which promoted the need for territorial and historical analysis of the formation of Vale do Aço region. The activity performed might be seen as important as it enables the reframing and the construction of CSO doers. Finally, the study questions the understanding of the CSO as an effective practice against non-recidivism, pinpointing that the variables related to criminality has ties to systemic logics. I t points out the need to have reservations against the speech of appreciation of this kind of penalty, because of the risk of reproducing an overcrowding in prison system which could be understood as borderless concentration camp